Ulun Lampung: A Website Based Social Studies Learning Media for Exploring the Local Wisdom of Pesisir Barat Culture Lampung - Wellfarina Hamer; Armila Armila; Wiwi Dwi Daniyarti (Attractive : Innovative Education Journal, 2026)
The website-based social studies (IPS) learning media was found to be feasible and effective for instructional use. Expert validation indicated consistently high quality, with scores of 86.1% (“Very High”) from media experts, 85% (“Very High”) from subject-matter experts, and 87.5% (“Very High”) from language experts. A small-group trial also produced a strong result (89.8%), categorized as “Very Good.” These findings support the importance of strengthening students’ understanding of local cultural wisdom as a basis for preserving traditional heritage in their communities. Nevertheless, many young people have limited knowledge of their own culture due to excessive imitation of foreign cultural influences. This study employed a research and development (R&D) approach using the PPE model (Planning, Production, and Evaluation). In the planning stage, a needs analysis was conducted through curriculum review, learning outcome analysis, and examination of student characteristics. In the production stage, the website was developed to enrich IPS learning resources on socio-cultural diversity by exploring Lampung culture in the West Coast (Pesisir Barat) region. The content included an introduction to Lampung culture, Kuntara Raja Niti (a customary law manuscript of the Lampung community), and regional exploration materials such as local profiles, customary practices, tourism diversity, culinary specialties, and cultural videos. In the evaluation stage, feasibility was assessed through expert judgment and a small-group trial. Effectiveness testing showed ( ), leading to rejection of and acceptance of . Therefore, the developed media is effective for use in the Basic Concepts of Social Studies course and is classified as “Very Good.”